2022
DOI: 10.1186/s43019-022-00165-z
|View full text |Cite
|
Sign up to set email alerts
|

Worse outcome of debridement, antibiotics, and implant retention in acute hematogenous infections than in postsurgical infections after total knee arthroplasty: a multicenter study

Abstract: Background We sought to determine (1) the success rate of debridement, antibiotics, and implant retention (DAIR) for acute periprosthetic joint infection (PJI) of the knee in patients with acute postsurgical infection and in those with acute hematogenous infection via a multicenter study, (2) the factors related to the failure of DAIR for overall acute PJI and acute hematogenous PJI via subgroup analysis, and (3) whether the PJI recurrence patterns differed between the two groups over time afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…over a total follow-up-period of 2 years (46.0% success in ALI vs. 76.0% in EI) [ 27 ]. Both Chang et al and Vilchez et al have also found that treatment success was higher in postsurgical (acute) PJI compared to hematogenous PJI [ 28 , 29 ]. Similarly, other studies have reported high relapse rates in patients with ALI, ranging from 21.0% up to 55.0% [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…over a total follow-up-period of 2 years (46.0% success in ALI vs. 76.0% in EI) [ 27 ]. Both Chang et al and Vilchez et al have also found that treatment success was higher in postsurgical (acute) PJI compared to hematogenous PJI [ 28 , 29 ]. Similarly, other studies have reported high relapse rates in patients with ALI, ranging from 21.0% up to 55.0% [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was the length of the follow-up, which was done for a minimum of six months and turned out to be a variable with statistically significant differences between the DACRI and DAPRI groups. Debridement usually fails for recurrences [ 35 ], and even if the authors considered six months of follow-up sufficient to detect the onset of an acute infection recurrence, it may not be enough time to exclude low-grade infection recurrences.…”
Section: Resultsmentioning
confidence: 99%
“…However, the purpose of this study was to detect loosening using only images. Seventh, most of the patients included in the study were women, as the majority of patients undergoing TKA in Asia are women [ 58 , 59 , 60 , 61 ]. Gender differences may affect the performance of the model, and further studies that include additional male patients are needed.…”
Section: Discussionmentioning
confidence: 99%